Strichartz Inequalities for the Wave Equation with the Full Laplacian on H-Type Groups - Heping Liu; Manli Song (Abstract and Applied Analysis)
We generalize the dispersive estimates and Strichartz inequalities for the solution of the wave equation related to the full Laplacian on H-type groups, by means of Besov spaces defined by a Littlewood-Paley decomposition related to the spectral of the full Laplacian. The dimension of the center on those groups is p and we assume that p>1. A key point consists in estimating the decay in time of the L∞ norm of the free solution. This requires a careful analysis due also to the nonhomogeneous nature of the full Laplacian.